Sostenibilidad en la cadena de suministro: evidencias del sector minorista español - Morcillo-Bellido, Jesús (360: Revista de Ciencias de la Gestión, 2018)
«Sustainability» in the supply chain is one of the important challenges of the 21st century. This work aims to deepen the understanding of how integral sustainability can be fostered, developed and supported through alliances and lean practices operations in a supply chain of the Services sector. Through the analysis carried out, it is sought to determine to what extent it has been possible to achieve a high level of comprehensive sustainability in the analyzed supply chain, supported by its own alliance model and the systematic and strict application of lean operations practices. The supply chain studied also presents the peculiarity of seeking that the efficiency practices developed in the focal company (Mercadona) are widely replicated in its more than one hundred key suppliers. The focal company is promoting the extension of these practices to its raw materials suppliers to achieve sustainability in the whole chain. The main contribution of this study is that it tries to show how integral